Religious Communities and Ministers of Worship - BACELAR GOUVEIA, Jorge (Revista Jurídica Portucalense, 2025)
The Religious Freedom Act, enacted by Law No. 16/2001 of 16 June, marked a pivotal moment in consolidating Portugal’s current legal framework on religion, grounded in a pluralistic and cooperative model of State–religion relations in accordance with the 1976 Constitution of the Portuguese Republic. Among its provisions, the regulation of religious communities and the status of their ministers of worship remain particularly sensitive and lesser-known areas. These aspects underscore the equal importance that must be accorded to the collective dimension of religious freedom.